Treatment of municipal wastewater using submerged membrane electro-bioreactor (SMEBR) for the control of membrane fouling and the removal of emerging contaminants - Ensano, Benny Marie B.
This study investigated the viability of treating recalcitrant pharmaceuticals from wastewater through the application of electrically enhanced membrane bioreactor (MBR). Diclofenac (DCF), carbamazepine (CBZ) and amoxicillin (AMX) were selected as representative drugs of frequently detected pharmaceuticals in the aquatic environment that cause adverse health effects even at relatively low concentrations. Varying experimental parameters, namely current density, contact time and initial pharmaceutical concentration, showed to have direct relationship with the removal of pollutants using intermittent electrocoagulation. Maximum removals (DCF= 90%, CBZ= 70% and AMX= 77%) were obtained at current density of 0.5 mA/cm2, initial concentration of 10 mg/L and reaction time of 38h. For eMBR, an environmentally relevant concentration (10 ug/L) of each compound was spiked into the synthetic wastewater and current densities equal to 0.5 mA/cm2 (eMBR-1) and 1.15 mA/cm2 (eMBR-2) were applied intermittently at 5 min ON/ 20 min OFF. A conventional membrane bioreactor (MBR) was operated as a control test. Higher removal of conventional and pharmaceutical pollutants and more enhanced fouling control were achieved by eMBR, as compared to the control MBR, due to the combined action of electrochemical processes (i.e. electrocoagulation, electrophoresis and electroosmosis) with biodegradation and membrane filtration in eMBR systems.